2021
DOI: 10.1016/j.dcn.2021.100977
|View full text |Cite
|
Sign up to set email alerts
|

Perception-action integration in young age—A cross-sectional EEG study

Abstract: Highlights Neurophysiology of developmental effects in event file coding is examined. Two distinct neurophysiological processes underlie developmental effects. Both processes are associated with the superior parietal cortex (BA7).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…Evidence for an involvement of TBA in action control has been corroborated by various studies using different paradigms. In recent years, a number of studies have corroborated a role of TBA activity properties in event-file processing, either by examining TBA directly using time-frequency EEG data 68,69 , or indirectly through EEG responses in the time domain known to depend on TBA [69][70][71][72][73][74][75] . In line with biophysical properties of TBA 59 , and its original conceptualization in TEC 15,43 , event-file dynamics reflect processing in a distributed cortical and subcortical network encompassing inferior and superior parietal areas, supplementary motor areas, the dorsolateral prefrontal cortex, and the hippocampus [69][70][71][72][73][74][75][76] .…”
Section: Box 1 | Glossary Of Conceptual Terms and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for an involvement of TBA in action control has been corroborated by various studies using different paradigms. In recent years, a number of studies have corroborated a role of TBA activity properties in event-file processing, either by examining TBA directly using time-frequency EEG data 68,69 , or indirectly through EEG responses in the time domain known to depend on TBA [69][70][71][72][73][74][75] . In line with biophysical properties of TBA 59 , and its original conceptualization in TEC 15,43 , event-file dynamics reflect processing in a distributed cortical and subcortical network encompassing inferior and superior parietal areas, supplementary motor areas, the dorsolateral prefrontal cortex, and the hippocampus [69][70][71][72][73][74][75][76] .…”
Section: Box 1 | Glossary Of Conceptual Terms and Definitionsmentioning
confidence: 99%
“…Nevertheless, the functional neuroanatomical level is also implied because theta and gamma band activity strongly refer to these activities in specific functional neuroanatomical structures (see section on theta/gamma band activity). Previous studies on event file coding as conceptualized in TEC, have consistently revealed that event-file dynamics reflect processing in a distributed cortical and subcortical network encompassing inferior and superior parietal areas, supplementary motor areas, the dorsolateral prefrontal cortex, and the hippocampus [69][70][71][72][73][74][75][76] . For alpha and beta band activity, however, the likely relevant functional neuroanatomical implementation Fig.…”
Section: Box 1 | Glossary Of Conceptual Terms and Definitionsmentioning
confidence: 99%
“…This event file reconfiguration reduces an automated response tendency and thereby increases the likelihood of a successful response inhibition in incongruent Simon Nogo trials. Interestingly, in the last years, several experiments have shown that event files are most likely reflected by C‐cluster activity in the EEG during response selection (Dilcher et al, 2021 ; Opitz et al, 2020 ; Takacs, Mückschel, et al, 2020 ; Takacs, Zink, et al, 2020 ) and response inhibition (Prochnow et al, 2021 ). Using EEG‐source localization, all of these studies have revealed that activity differences in inferior parietal cortices are associated with these modulations.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the appropriate response thus requires to reconfigure event the EEG during response selection (Dilcher et al, 2021;Opitz et al, 2020;Takacs, Zink, et al, 2020) and response inhibition (Prochnow et al, 2021). Using EEG-source localization, all of these studies have revealed that activity differences in inferior parietal cortices are associated with these modulations.…”
Section: Implications For Cognitive Science Theorymentioning
confidence: 99%
“…According to our expectations, event file binding processes should be reflected by the P3 component. We base this decision on numerous findings by our group and others showing that event file processes consistently affect neurophysiological dynamics in the P3 time window during both, response selection 36,37,53 and response inhibition. 39,54 Of note, P3 modulations were also found in other movement disorders.…”
Section: Eeg Data Recording and Ridementioning
confidence: 99%